The efficacy and safety of paclitaxel plus bevacizumab therapy in breast cancer patients with visceral crisis. (August 2021) - Funasaka, Chikako; Naito, Yoichi; Kusuhara, Shota; Nakao, Takehiro; Fukasawa, Yoko; Mamishin, Kanako; Komuro, Ayumi; Okunaka, Mashiro; Kondoh, Chihiro; Harano, Kenichi; Kogawa, Takahiro; Matsubara, Nobuaki; et al.
Abstract: Background: Visceral crisis in metastatic breast cancer (MBC) is defined as severe organ dysfunction requiring rapidly efficacious therapy. Although weekly paclitaxel plus bevacizumab (wPTX + BV) achieves a high response rate in human epidermal growth factor receptor 2 (HER2)-negative MBC, the efficacy and safety of wPTX + BV for visceral crisis is unclear. Methods: We retrospectively investigated patients with MBC with visceral crisis who received wPTX + BV. Visceral crisis was defined as follows: liver dysfunction (aspartate or alanine aminotransferase >200 U/L or total bilirubin >1.5 mg/dl), respiratory dysfunction (carcinomatous lymphangiomatosis, SpO2 <93% in ambient air or required thoracentesis), superior vena cava (SVC) syndrome, or bone marrow carcinomatosis. The primary outcome was the proportion of patients on-treatment with wPTX + BV after 12 weeks. We also investigated time to treatment failure (TTF), overall survival (OS), objective response rate (ORR), and adverse events. Results: A total of 44 patients with respiratory dysfunction (n = 29), liver dysfunction (n = 10), bone marrow carcinomatosis (n = 7), and SVC syndrome (n = 2) were eligible for this investigation. The proportion of patients on-treatment with wPTX + BV after 12 weeks was 63% (30/44), and the other patients discontinued wPTX + BV because of adverse events (n = 5) and disease progression (n = 9). Median TTF and OS, and the ORR were 131 days and 323 days, and 41%, respectively. No treatment-related death occurred. Conclusion: wPTX + BV achieved favorable efficacy and safety for treating patients with visceral crisis and may therefore be considered an option for the treatment of this acutely severe clinical condition. Highlights: Visceral crisis is a severe organ dysfunction requiring rapidly efficacious therapy. The efficacy of chemotherapy in visceral crisis is unclear. Weekly paclitaxel plus bevacizumab (wPTX + BV) achieved favorable efficacy and safety. wPTX + BV may be considered an option for breast cancer patients with visceral crisis.